Pengolahan Limbah Cair Logam Berat (Limbah B3) Secara Presipitasi Dan Koagulasi Di Upt pengujian Dinas pekerjaan Umum (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Waste generated from the remainder of the testing BOD, COD, AAS and Organic Matter from a laboratory activity category B3 waste (hazardous and toxic materials) because they contain heavy metals that can pollute the environment and therefore the waste should not be thrown away immediately to the environment. This thesis aims to guide the initial processing of waste by the process of precipitation, neutralization with NaOH 26.36% w / w, coagulation and flocculation using PAC uses polymer. Where would perform variations of precipitant material is sulphide, carbonate and combined to see the effect of the concentration of heavy metal pollutants are dissolved heavy metals such as iron (Fe), cadmium (Cd), Ma Â¬ with (Mn), chromium (Cr), Copper (Cu) , Cobalt (Co), Zinc (Zn), Lead (Pb) and Nickel (Ni) at baseline prior to treatment of waste on the concentration of pollutants after sewage treatment through each precipitation method and look for the best methods of precipitation. At the beginning of the test characteristics of heavy metal concentrations obtained its initial waste Cr at 40.5742 mg/L, 22.4494 mg/L Fe, Mn metal 2,8392 mg/L, 2,2239 mg/L Cu then, Pb 1.0957 mg/L, 0.6135 mg/L Zn metal, metallic Ni 0 , 4994 mg/L, 0.4795 mg/L Metals Co., and metals Cd <0.001 mg/L. Of the three methods of precipitation is done to reduce heavy metal pollutants derived precipitation method is the most well combined sulphide and carbonate precipitation where heavy metal test results end processing for metals cadmium (Cd) <0.001 mg/L, Copper (Cu) 0.4455 mg/L, iron (Fe ) 8.5263 mg/L, Manganese (Mn) 0.7292 mg/L, Lead (Pb) 0.6033 mg/L, zinc (Zn) 0.3076 mg/L, chromium (Cr) 0,026 mg/L, nickel (Ni) 0.2217 mg/L, Cobalt (Co) 0.1918 mg/L.Keywords: heavy metal waste treatment, laboratory wastes, precipitation.